2019
DOI: 10.3389/fpsyt.2019.00719
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Temporal Dynamics of Resting State Shapes Stimulus-Evoked Activity in Depression—An EEG Study on Rest–Stimulus Interaction

Abstract: Major depressive disorder (MDD) is a complex psychiatric disorder characterized by changes in both resting state and stimulus-evoked activity. Whether resting state changes are carried over to stimulus-evoked activity, however, is unclear. We conducted a combined rest (3 min) and task (three-stimulus auditory oddball paradigm) EEG study in n=28 acute depressed MDD patients, comparing them with n=25 healthy participants. Our focus was on the temporal dynamics of both resting state and stimulus-evoked activity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 105 publications
(159 reference statements)
2
28
0
Order By: Relevance
“…Greater resting-state values of LZC on the whole scalp in MDD patients were also observed by Bachmann et al [117]. Wolff et al [118] analyzed LZC values from EEG recorded during an auditory oddball paradigm, finding that LZC changes after stimulus onset were significantly lower in MDD group, but for deviant stimuli only. Cukic and colleagues [119] compared the HFD and SampEn values at resting-state in patients suffering from acute depressive episode, patients in remission and healthy participants.…”
Section: ) Eeg Complexity Metricsmentioning
confidence: 63%
“…Greater resting-state values of LZC on the whole scalp in MDD patients were also observed by Bachmann et al [117]. Wolff et al [118] analyzed LZC values from EEG recorded during an auditory oddball paradigm, finding that LZC changes after stimulus onset were significantly lower in MDD group, but for deviant stimuli only. Cukic and colleagues [119] compared the HFD and SampEn values at resting-state in patients suffering from acute depressive episode, patients in remission and healthy participants.…”
Section: ) Eeg Complexity Metricsmentioning
confidence: 63%
“…The second component of ongoing activity can be found in pre-stimulus activity, that is, neural activity immediately preceding the onset of a specific stimulus or task, that is, 100–1000 ms before the onset of the stimulus [ 52 , 53 , 54 , 55 , 56 , 57 ]. This can be coined as the ‘temporo-spatial context’ as it precedes stimulus-induced activity but provides a temporo-spatial context for the latter.…”
Section: Neuronal Mechanisms—from Pre-stimulus To Stimulus-induced Ac...mentioning
confidence: 99%
“…For the first choice, an EEGLAB based automatic artifact rejection pipeline ADJUST, developed by Mognon et al was used [54]. The first step in this method was to run independent component analysis (ICA) and extract different components of the signals [39,55]. To properly decompose the components, Onton et al suggested that the number of extracted components, n should be such that n 2 k = number of time points, k 20 [56].…”
Section: Eeg Preprocessingmentioning
confidence: 99%
“…However, this time, the filters were band-pass filters instead of a notch filter. Similar to the methods employed by Hussain et al and Wolff et al, the filtered signals of the four frequency bands were Hilbert's transformed to obtain phases (in degrees) from −750 ms to 0 ms [18,47,55]. The shorter time window of length 250 ms was not selected during phase estimation because a signal of length 250 ms will contain only 0.6 to 1.2 cycles of the theta frequency band potentially resulting in inaccurate phases.…”
Section: Frequency Band Phase Estimationmentioning
confidence: 99%